2020
DOI: 10.1186/s12877-020-01844-w
|View full text |Cite
|
Sign up to set email alerts
|

Community-dwelling older adults’ awareness of the inappropriate use of proton pump inhibitors

Abstract: Background Proton pump inhibitors (PPIs) are effective in treating gastroesophageal reflux, peptic ulcers, and esophagitis. However, the long-term use of PPIs by older adults is associated with adverse health outcomes. There is limited evidence about older adults’ awareness of long-term PPI use and its associated adverse effects. This study aimed to assess older adults’ awareness of the adverse effects of the long-term use of PPIs, and their willingness to stop PPI use given of the risks and benefits of PPI us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, their use for more than 8 weeks should be avoided because they are associated with Clostridium difficile infection and bone loss and fracture (Fick et al 2019). Patient education and increasing healthcare knowledge about long-term side effects of PPIs is necessary especially that studies show a lack of awareness of inappropriate use PPIs and their related adverse events among patients (Rababa and Rababa'h 2020) and healthcare providers including physicians, pharmacists and nurses (Luo et al 2019;Asdaq et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, their use for more than 8 weeks should be avoided because they are associated with Clostridium difficile infection and bone loss and fracture (Fick et al 2019). Patient education and increasing healthcare knowledge about long-term side effects of PPIs is necessary especially that studies show a lack of awareness of inappropriate use PPIs and their related adverse events among patients (Rababa and Rababa'h 2020) and healthcare providers including physicians, pharmacists and nurses (Luo et al 2019;Asdaq et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults generally expect the prescribers to prescribe them with PPIs and PPIs dramatically improve their quality of life. 35 The proportion of medications to be used with caution was 19.55%, and diuretics were the most frequently prescribed medications. Similar to our study results, another study reported that the prevalence of PIMs that should be avoided was 60.7%, with gastrointestinal drugs commonly prescribed, and the prevalence of PIMs that should be used with caution was 40.6%, with diuretics, antidepressants and antiplatelet drugs commonly prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…However, physicians’ and patients’ awareness regarding this issue remains poor. In a survey on 120 elderly patients, the majority of the participants were not familiar with any reports linking long-term proton pump inhibitor use with adverse effects, reported no concerns related to their chronic use, and stated that they had not discussed the benefits and risks of this therapy with their primary care providers [ 40 , 41 ]. It is also to be acknowledged that older adults often report feeling uncomfortable discussing whether to stop proton pump inhibitors with their providers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%